2017
DOI: 10.1302/0301-620x.99b6.bjj-2016-0569.r1
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic decompression not recommended in the treatment of rotator cuff tendinopathy

Abstract: The natural history of rotator cuff tendinopathy probably plays a significant role in the results in the long-term. Even though the patients who underwent operative treatment had a stronger belief in recovery, which is likely to be surgical and the effect of placebo, the exercise group obtained similar results. In the future, an optimum exercise regime should be searched for, as the most clinically and cost-effective conservative treatment for rotator cuff tendinopathy. Cite this article: 2017;99-B:799-805.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…In the short-term (up to 2 years), ASD did not alleviate shoulder symptoms any more than placebo surgery. 12 21 The existing long-term evidence of the effects of ASD, consisting of 5-10 years follow-up studies comparing ASD to exercise therapy, [7][8][9][10] is conflicting. In three of these unblinded trials, there was no clinically meaningful benefit, 7 8 10 while one trial suggested a benefit of ASD.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short-term (up to 2 years), ASD did not alleviate shoulder symptoms any more than placebo surgery. 12 21 The existing long-term evidence of the effects of ASD, consisting of 5-10 years follow-up studies comparing ASD to exercise therapy, [7][8][9][10] is conflicting. In three of these unblinded trials, there was no clinically meaningful benefit, 7 8 10 while one trial suggested a benefit of ASD.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The existing long-term evidence consists of 5-10 years follow-up studies comparing ASD to exercise therapy. [7][8][9][10] In three of these unblinded trials, there was no clinically meaningful benefit, 7 8 10 while one trial suggested a benefit of ASD. 9 Updates to the BMJ RapidRec guideline and the Cochrane review are pending low risk of bias evidence on the long-term outcomes on subacromial decompression surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, authors challenged the need for surgery in SAIS. A more comprehensive understanding of the pathogenesis lead to the publication of several papers which questioned the benefit of decompression surgery and the rationale of the “impingement” mechanism stating that placebo effect, prolonged rest, and intense physiotherapy after surgery have to be considered the true treatments 2227…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative analysis was hence performed. The minimum follow-up was 6 months27 and the longest was 13 years 22. Studies with large group of patients enrolled and long-term follow-up were preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific basis for the fundamental components of the impingement syndrome has, however, been questioned 220 . Increasing highlevel evidence, including placebo surgery trials, has also failed to show any clinically significant effect of the classical anterior acromioplasty above the effect seen with structured physiotherapy, both as treatment for subacromial pain 15,147,219 and as an adjunct to cuff repair 36 . In recent years the lateral extension of the acromion has come into focus instead 216 .…”
Section: Prevalence and Predisposing Factors For Rotator Cuff Tearmentioning
confidence: 99%